DEVELOPMENT OF MEDIA MIND MAP WITH FREEMIND APPLICATIONS ON ENGLISH LANGUAGE COURSE IN ENGLISH EDUCATION STUDIES PROGRAM UNIVERSITY OF PALEMBANG - Nelya Juita; Dian Eka Putra (Sriwijaya University Learning and Education International Conference, 2018)
This research aims to develop instructional media with application of FreeMind on English course in order to produce a valid, practical, and potential effect. Before tested the product first be validated by experts on two aspects: the material and the design aspects of the media which score of 3.65 on a valid category in media and material aspect. Results obtained from the development stage to be obtained that the media mind map with FreeMind application developed otherwise proven its practicality, is seen from the results of the evaluation of a small group of filling the questionnaire given to the students obtained a value of 81,94with a practical category. Supported the observation of the average activity of students is 78.472%which means that the media used by students in learning activities in the classroom in a practical category (71-85). To determine the potential effect on the media mind map by using the Freemind application indicated by a score of learning outcomes English course in the category, it is based on the results of the calculation of the value of N gain on the material 1 equal to 0.403/Effective in medium category.